The hinders of speaking Arabic language in a good command through 11 th and 12 th grades students opinions, at Malik bin Anas School for Basic Education in Al Buraimi Governorate, Sultanate of Oman - Alsaadi, Ahmed Hamed Said; Al-Saadi, Ahmed bin Saif bin Ali (Journal of Educational and Psychological Sciences, 2019)
This study aims to revealing the obstacles facing 11th and 12th graders in speaking Standard Arabic in Malik bin Anas School for Basic Education, Governorate of Al Buraimi. The researchers set up a questionnaire made up of 17 elements which fall into two sections. The first is concerned with the inside-school obstacles, the second with the outside-school obstacles. The researchers carried out their study on an elected sample of students from the school and answered the following questions:1- According to 11th and 12th graders, what are the obstacles facing them in speaking Standard Arabic?2- Do the sample-students’ assessment of the different obstacles in speaking Standard Arabic differ in accordance to their gender and competence?In conclusion, the study recommends that teachers and school administrative stuff alike should converse in Standard Arabic amongst themselves and with students as well. Furthermore, it urges a continuous encouragement for students to take part in literary competitions (such as debates and presentations) held by the Ministry of Education and the implementation of further research in the field.
Keywords: Obstacles; Standard Arabic